Nutrient gaps are prevalent among women experiencing infertility, a cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES), 2013–2020 - Rachel A. Murphy; Carroll A. Reider; Ryan W. Grant; Susan Hazels Mitmesser (PLoS ONE, 2026)
Background Adequate nutrient intake is important for supporting reproductive health. Few studies have examined the role of nutrients for fertility among women, resulting in a critical evidence gap. The aim of this study was to explore the usual intake and prevalence of nutrient inadequacies from foods only and foods plus dietary supplements among women of child bearing age with and without infertility. Methods This cross-sectional study used data from the National Health and Nutrition Examination Survey (NHANES), a national survey in the United States. Participants included women aged 18–44 years from 2013–2020 with or without infertility (difficulty trying to conceive for at least one-year). The mean usual intakes and prevalence of inadequacy (% < EAR/AI) of key nutrients- vitamins A, B1, B2, niacin, B6, B12, C, D, E, K, lycopene, lutein + zeaxanthin, folate, choline, zinc, selenium, iron, calcium, magnesium, EPA and DHA were determined from 24-hr dietary recalls. Results Women aged 18–44 years who reported infertility had significantly lower intakes of vitamin A, E and K and lutein and zeaxanthin from foods and foods + supplements compared to women without infertility. Lower intakes of selenium (foods only, 96.6 ug/d vs 100 ug/d), vitamin C (foods only, 66.9 mg/d vs. 74.2 mg/d) and calcium (foods + dietary supplements, 941 mg/d vs. 974 mg/d) were also observed in women reporting infertility. Fewer women with infertility met nutrient requirements. For example, 21.5% of women with infertility were below the EAR for vitamin B6 versus 14.6% of women without infertility and over 50% of those with infertility were below the EAR/AI for vitamins A, C, E, and magnesium and potassium. Differences in nutrient intakes by fertility status were particularly pronounced for women aged 35–44 years. Conclusions These findings suggest lower intake of key nutrients among women with infertility, especially those aged 35–44. Future studies are needed to understand the implications of nutrient gaps for conception. Across all age groups, and fertility status, gaps in nutrients that are important for overall health were evident, underscoring the need for public health strategies to address broad dietary improvements.